2021
DOI: 10.1016/j.celrep.2021.110150
|View full text |Cite
|
Sign up to set email alerts
|

Orally acquired cyclic dinucleotides drive dSTING-dependent antiviral immunity in enterocytes

Abstract: Highlights d Cyclic dinucleotides (CDNs) are sensed by enterocytes to induce antiviral protection d CDNs signal through dSTING and NF-kB to induce gene expression d Antiviral activity of CDNs is dependent on the apical nucleoside transporter CNT2 d Antiviral activities of CDNs and dSTING are tissue specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Besides its intracellular role, 2′3′-cGAMP also exists as a soluble, extracellular immunotransmitter [22][23][24] . Therefore, it is possible that apart from being the melanization inhibitor in insects, the secretory P26/poxin homologs might also be involved in degrading extracellular 2′3′-cGAMP in mammals and insects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its intracellular role, 2′3′-cGAMP also exists as a soluble, extracellular immunotransmitter [22][23][24] . Therefore, it is possible that apart from being the melanization inhibitor in insects, the secretory P26/poxin homologs might also be involved in degrading extracellular 2′3′-cGAMP in mammals and insects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the important role played by the Stimulator of interferon genes (STING) pathway in the antiviral defence of D. melanogaster opens new perspectives [32]. Indeed, STING-dependent signalling can be activated in vivo by injection of cyclic dinucleotides [33][34][35][36]. This provides a powerful means to trigger antiviral immunity in a range of insects, paving the way for evo-immuno (figure 1).…”
Section: Evolutionary Immunology To Delve Into the Biodiversity Of An...mentioning
confidence: 99%
“…Knockout experiments have provided evidence that DmSTING exerts its antiviral activity through an NF‐κB‐dependent mechanism, specifically involving the transcription factor Relish 28,39 . Similarly, BmSTING, a STING homolog in Bombyx mori , also presents NF‐κB‐dependent antiviral signaling upon nucleopolyhedrovirus (NPV) infection.…”
Section: Primary Antiviral Activity Of the Cgas–sting Pathway From An...mentioning
confidence: 99%
“…Previous studies have shown that Drosophila STING (DmSTING) is capable of activating the immune response upon CDN stimulation. 38,39 Recently, a series of studies have further identified two cGLRs in Drosophila as cGAS homologs to detect nucleic acids and synthesize divergent second messengers, including 3′2′-cGAMP, 2′3′-cGAMP, 2′3′-c-di-GMP, and 2′3′-c-di-AMP. 34,40,41 DmSTING recognizes these second messengers, although its specific preferences remain unidentified, and ultimately exhibits antiviral activity.…”
Section: Primary Antiviral Activity Of the Cgas-sting Pathway From An...mentioning
confidence: 99%